Kinetic Properties of the Isoenzymes of Human Creatine Phosphokinase - Witteveen, S. A. G. J. (1974)
Studies of the three human creatine phosphokinase (EC 2.7.3.2) isoenzymes, MM, MB, and BB, show that important differences exist in substrate dependency of the reaction rates. A method was developed to study these properties in which the ATP formed in the reverse reaction was measured by means of firefly luciferase. With substrate conditions at which the isoenzymes showed substantial differences in activity the method could be used for the detection of changes in the isoenzyme pattern of the serum of patients with an acute myocardial infarction. The MB isoenzyme appearing in this condition could be detected quantitatively.